Study of spatially confined copper plasma by probe beam deflection technique - Alnama, Koutayba; Ibrahim, Ihab; Sulaiman, Nawar (European physical journal. Applied physics, 2024)
In the last decade, laser induced plasma (LIP) has emerged as one of the most promising techniques for various applications. It is now commonly investigated using various expensive techniques. Probe beam deflection (PBD) is an inexpensive technique generally utilized to characterize the shock wave. In this work, the copper laser-induced plasma plume and shock wave are both investigated using PBD technique. The plasma is generated at atmospheric pressure using Nd:YAG laser at a low laser power density (0.8 GW/cm 2 ). The contribution of the plasma plume components to the PBD signal is clarified in space and time. The spatial confinement effect by a metallic disk is also investigated. It approves the physical mechanisms responsible for the deflection signal. As well, the spatial distribution of the weak shock wave velocity is considered.